MEDIA PEMBELAJARAN BERBASIS LINGKUNGAN MELALUI MODEL ASSURE PADA PELAJARAN FIKIH - maftuh, Maftuh; Alfiani, Nurul (MIYAH: Jurnal Studi Islam, 2025)
This journal aims to examine the application of environmental-based learning media through the ASSURE model in fiqh learning as a learner-centered approach. Considering the function of implementing the ASSURE model as an effective intermediary in conveying knowledge. This study attempts to answer the following questions: (1) How is environmental-based learning media through the ASSURE model in fiqh learning? (2) How is the evaluation of environmental-based learning carried out through the ASSURE model in fiqh learning. To answer these questions, the researcher conducted field research using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The results of the study showed that there were six steps in implementing the ASSURE model, namely: analyzing student characteristics, setting learning objectives, choosing methods, media, and materials, utilizing media and materials, requiring student participation, and evaluating and revising. Furthermore, the evaluation of the ASSURE model in fiqh learning includes adding study hours to improve student understanding, so that they can understand the material more easily and effectively. Keywords: Pembelajaran berbasis lingkungan, Model ASSURE